Biogenesis of circular RNAs and their roles in cardiovascular development and pathology. (23rd August 2017) - Li, Mengyang; Ding, Wei; Sun, Teng; Tariq, Muhammad A.; Xu, Tao; Li, Peifeng; Wang, Jianxun
Abstract : Circular RNAs (circRNAs) are a newly discovered type of RNA generated by back‐splicing of precursor mRNA and found in many species. They are, expressed in a tissue‐specific manner and fulfill regulatory activities in many biological processes. Recent research has revealed that circRNAs play critical roles in the development and pathologies of the cardiovascular system. Some of these circRNAs show aberrant expression and regulatory activities during heart disease including heart failure and cardiac infarction and hypertrophy. These findings suggest that circRNAs might be a suitable target for the treatment and prevention of heart disease. In this review, we summarize the latest research on the biogenesis and functions of circRNAs with emphasis on the regulatory roles of circRNAs in the development and pathologies of the cardiovascular system. Abstract : Circular RNA (circRNA) is a new type of RNA that has been identified in many organisms. Its versatile activities in the cardiovascular system have been reported, including acting as miRNA sponges, protein binding, acting as transcription enhancers and peptide encoding. In this review, we summarize the latest research on the biogenesis and functions of circRNAs with emphasis on their regulatory roles in the development and pathologies of the cardiovascular system.